A phase II exploratory cluster randomized controlled trial of a group mobility training and staff education intervention to promote urinary continence in UK care homes - Sackley, Catherine M; Rodriguez, Natalie A; van den Berg, Maayken; Badger, Frances; Wright, Christine; Besemer, Jelske; van Reeuwijk, Katarina TV; van Wely, Leontine (Clinical rehabilitation, 2008)
Objectives: To assess feasibility, acceptability and potential efficacy of group exercise and staff education intervention to promote continence in older people residing in care homes. To establish measures and information to inform a larger trial. Design: Phase II pilot exploratory cluster randomized controlled trial. Setting: Six purposively selected care homes in the West Midlands, UK. Subjects: Thirty-four care home residents (mean age 86, 29 female), 23 with cognitive impairments. Intervention: Physiotherapy-led group exercise and staff continence and mobility facilitation training. Main outcome measures: Reported continence status, Rivermead Mobility Index. Feasibility was assessed by uptake and compliance, and acceptability by verbal feedback. A staff knowledge questionnaire was used. Results: Thirty-three residents, cluster sizes from 3 to 7. The number of residents agreeing with the statement `Do you ever leak any urine when you don't mean to?' in the intervention group decreased from 12/17 at baseline to 7/17 at six weeks in the intervention group and increased from 9/16 at baseline to 9/15 at six weeks. The Rivermead Mobility Index scores were better in the intervention group (n = 17; baseline: 6.1, six weeks: 6.2) compared with controls (n = 16; baseline: 5.9, six weeks: 4.75). The intervention was feasible, well received and had good compliance. Conclusions: Group mobility training and staff education to promote continence is feasible and acceptable for use with care home residents, including those with cognitive impairment.